Keputusan Pembelian Facial Wash Nivea Man di Kabupaten Kolaka : Dilihat Dari Gaya Hidup Dan Faktor Sosial - Nurhasanah Nurhasanah; Niar Astaginy; Hanif Kurniadi (University of Riau Kepulauan, 2026)
This study aims to examine the influence of lifestyle and social factors on purchasing decisions for Nivea Men's Facial Wash in Kolaka Regency. A quantitative research approach was employed, with data collected through questionnaires. The study targeted consumers of Nivea Men's Facial Wash in Kolaka Regency, selecting a sample of 100 respondents using a purposive sampling technique. The findings indicate a significant positive relationship between lifestyle and social factors and purchasing decisions for Nivea Men's Facial Wash in the region.